Millennial-scale variability in biomass burning covering the interval ~41,000-7050 cal BP in the tropical Leizhou Peninsula (south China) - Xue, Jibin; Zhong, Wei; Xie, Lichun; Unkel, Ingmar (Palaeogeography, palaeoclimatology, palaeoecology, 2015)
Here, we present a well-dated terrestrial charcoal chronology covering the interval ~41,000-7050cal BP and identifying the millennial-scale variability in biomass burning for the tropical Leizhou Peninsula, south China. Our results show that changes in biomass burning closely followed regional temperature and precipitation variations on orbital timescales, i.e., more biomass burning occurred during the warm/wet Marine Isotope Stage (MIS) 3, and less biomass burning occurred during the cold/dry MIS 2. Superimposed on this general trend, our charcoal record shows millennial-scale variability in biomass burning corresponding to the rapid climate changes associated with Dansgaard-Oeschger (D-O) cycles, i.e., biomass burning increased during D-O warming events, whereas biomass burning decreased during intervals of rapid cooling terminated by Heinrich events. During the cooler/drier periods, low biomass burning can be explained by the decline of vegetation productivity, whereas the warmer/wetter periods are characterized by higher biomass burning related to increasing fuel availability. Therefore, climate control can be considered as the major forcing factor of biomass burning from 41,000-7050cal BP on both orbital and millennial timescales in the northern Leizhou Peninsula.
Online verfügbar: 5. September 2015, Artikelversion: 9. September 2015
Gesehen am 19.02.2025